Charted Port Positions in the Pacific As Defined by Satellite Determined Positions Using Multiple Observations - Godley, Valerie M. (The International Hydrographic Review, 2015)
Positions for 34 docks or anchorage sites in and around the Pacific basin were defined by multiple position determination using the Magnavox 702 Satellite Navigator as a fixed-point positioning device. A significant number of positions represent improvements of 15 seconds or more in the charted positions of islands, ports and harbors in the Pacific basin. This study will contribute to the safety of land-approach navigation by providing more modern and accurate positional information than can be obtained from curren t charts.